2015
DOI: 10.1177/0021998315579927
|View full text |Cite
|
Sign up to set email alerts
|

Predicting permeability based on flow simulations and textile modelling techniques: Comparison with experimental values and verification of FlowTex solver using Ansys CFX

Abstract: This paper compares the predicted permeability values obtained from conducting simulations with experimental results from the second permeability benchmark exercise. An automated tool, which has been developed for this purpose and is presented here, carries out flow simulations on WiseTex generated meshes using Ansys CFX. Different meshing methods are explored, and the effects of different boundary conditions, number of layers used to model the preform and the incorporation of nesting are examined. The predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Possible reasons for this discrepancy include modeling unable to capture the actual phenomena in full extent and simulation inputs that differ from their corresponding actual values. Indicatively, Swery et al [56] showed that the preform permeability, a simulation input affecting heavily the results, is overestimated by a factor of two when model-derived instead of experimentally determined. However, in order to benefit the system-to-be, design choices made in development must be based on accurate predictions.…”
Section: Work To Minimize the Negative Impact Of Input Uncertaintiesmentioning
confidence: 99%
“…Possible reasons for this discrepancy include modeling unable to capture the actual phenomena in full extent and simulation inputs that differ from their corresponding actual values. Indicatively, Swery et al [56] showed that the preform permeability, a simulation input affecting heavily the results, is overestimated by a factor of two when model-derived instead of experimentally determined. However, in order to benefit the system-to-be, design choices made in development must be based on accurate predictions.…”
Section: Work To Minimize the Negative Impact Of Input Uncertaintiesmentioning
confidence: 99%
“…The development procedure for the specific tool including design aspects, deflection, heat transfer, and filling simulations was as well described in the past. 16 The parameters characterizing the draping of the specific curvatures, as defined in equation (2), are: R = 25 mm, h = 3 mm, L = 22 mm, and θ = 45°. The tool supports heating by liquid that flows through heating channels opened in the tool body while it was designed to host different sensors, namely dielectric analyzer, direct current sensor, ultrasound sensor, and pressure transducers.…”
Section: Computational Aspectsmentioning
confidence: 99%
“…However, simulations may differ from reality; poor compatibility between simulation inputs and actual conditions, models that fail to describe accurately the actual behavior and the inherent structural uncertainty of fibrous preforms are the main origins of such differences. 2 A decisive input parameter for simulations is permeability; an intrinsic preform characteristic inversely proportional to the flow resistance that the fluid is subjected to by the fibrous preform. Since it is heavily affected by the structural uncertainty of the preform, permeability has been found to vary significantly.…”
Section: Introductionmentioning
confidence: 99%
“…But authors noted that there is a restriction on grid size and the use of physical models. Using this approach in [5] Elinor E. Swery performed permeability calculating for different 2D textiles. Numerical results without intra-yarn flow show good agreement with direct modelling in ANSYS CFX.…”
Section: Introductionmentioning
confidence: 99%